Therapeutic Potential of the Gut Microbiota in the Management of Sepsis - Bassetti, Matteo; Bandera, Alessandra; Gori, Andrea (Critical care (London, England), 2020)
This article is one of ten reviews selected from the Annual Update in Intensive Care and Emergency Medicine 2020. Other selected articles can be found online at https://www.biomedcentral.com/collections/annualupdate2020 . Further information about the Annual Update in Intensive Care and Emergency Medicine is available from http://www.springer.com/series/8901 .